Attention deficit in children: a multiprofessional approach - Sachithanandam, Sangeetha Thirumazhisi (International Journal of Research in Medical Sciences, 2017)
Attention Deficit Hyperactivity Disorder (ADHD) is the most common behavior disorder in children characterized by attention deficit, overactivity and impulsivity, which may persist into adolescence and adulthood. It is often complicated with multiple comorbid disorders which when undiagnosed or untreated significantly affects the children on aspects like academic skills, peer relationship, social life and difficulty in leading productive lives. This report presents a case of 12 year old male child with attention deficit and poor academic performance, diagnosed and treated for ADHD with a complex array of coexisting disorders untreated. An attempt is made to highlight the differential diagnosis for attention deficit in children, comorbid disorders, and the necessity for a multiprofessional approach in complete evaluation and comprehensive management of the same.